MONITORING LANDING OF SEA TURTLES LAYING EGGS IN THE PANGANDARAN REGION - Lisa Desanti; Junianto Junianto (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Green turtles and Olive Ridley turtles that are often found on Pangandaran Beach to lay their eggs. The aim of this research is to determine the process of monitoring turtle eggs laying in the Pangandaran Beach area. This activity was carried out at Batuhiu Beach and Legokjawa Beach in May-July 2023. The methods used were surveys and observations, as well as interview with fishermen groups in the surrounding area. The results obtained were that the Green Turtle produced 96 eggs on July 3 2023 at Legokjawa Beach, and 73 Olive Ridley Turtle eggs on July 28 2023 at Batuhiu Beach. This means that these results can show that Pangandaran Beach has the potential to become a turtle conservation area, and requires a lot of special attention to preserve turtles so that they do not experience extinction.